Managing potential impacts and uncertainties of high-speed rail access at local level: Insights from four German cities - Weiß, Manuel; Münter, Angelika; Strambach, Simone (ERDKUNDE, 2025)
This paper empirically investigates how local actors manage potential impacts and uncertainties associated with a new high-speed rail (HSR) access. The provision of such supra-regional transport infrastructure offers significant benefits to accessed cities and regions. However, the main challenge lies in transforming the potentials into actual local impacts. We conducted expert interviews in four German cities equipped with HSR stations to examine ways and practices of local responsible actors in this context. The study focuses on the voiced objectives and approaches, the instruments and actions used, and the factors that facilitate or impede leveraging potential impacts. Using the conceptual framework of strategic planning, we show that both linear and adaptive strategies are required to cope with uncertainties. Furthermore, anticipation of potential impacts by politicians and planners with a long-term horizon can prove advantageous in the face of complex dynamics. Promising and necessary progress could be made through enhanced cooperation and coordination with Germany’s HSR operator and by taking greater account of local concerns with regard to a stronger integration of HSR-related transport and spatial planning.